PENGEMBANGAN DAN UJI EFEKTIVITAS GAME EDUKASI DIGITAL “PARTA (PINTAR PERSAMAAN KUADRAT)” SEBAGAI SARANA BELAJAR MANDIRI PADA MATERI PEMFAKTORAN UNTUK SISWA SMA KELAS X - Ferdyan, Yohanes Bekta; Setyadi, Danang (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2026)
This study aims to develop a digital educational game “PARTA (Pintar Persamaan Kuadrat)” as an independent learning tool for senior high school students on quadratic factorization. The development model employed was ADDIE (Analysis, Design, Development, Implementation, Evaluation) combined with Tessmer’s formative evaluation, consisting of expert validation, one-to-one testing, small group testing, and field testing. The research subjects involved 3 students in the one-to-one stage, 10 students in the small group stage, and 66 students in the field test stage. The instruments used were expert validation sheets, student response questionnaires, and learning achievement tests (pretest and posttest). The validation results indicated that the media was highly feasible in terms of content, visual design, and technical quality. Student responses were positive, with high ratings in understanding, attractiveness, comfort, and motivation. The effectiveness test revealed a significant improvement in learning outcomes, where the average pretest score of 30.61 increased to 78.64 in the posttest. The Wilcoxon Signed Rank Test showed Z = -6.969 with Sig. 0.000 ( 0.05), confirming that PARTA effectively enhanced students’ understanding of quadratic factorization. Thus, the media is declared feasible and effective as an alternative digital-based independent learning tool suitable for Generation Z and Alpha characteristics.